Risk for Infection with Highly Pathogenic Avian Influenza Virus (H5N1) in Backyard Chickens, Bangladesh - Biswas, Paritosh K. (Centers for Disease Control and Prevention, 2009)
To evaluate risk factors for infection with highly pathogenic avian influenza A virus (H5N1) in backyard chickens in Bangladesh, we conducted a matched case–control study. We enrolled 25 case farms (cases March–November 2007) and 75 control farms (June–November 2007). We used a questionnaire to collect farm data, which were analyzed by matched-pair analysis and multivariate conditional logistic regression. Factors independently associated were offering slaughter remnants of purchased chickens to backyard chickens (odds ratio [OR] 13.29, 95% confidence interval [CI] 1.34–131.98, p = 0.027), having a nearby water body (OR 5.27, 95% CI 1.24–22.34, p = 0.024), and having contact with pigeons (OR 4.47, 95% CI 1.14–17.50, p = 0.032). Separating chickens and ducks at night was protective (OR 0.06, 95% CI 0.01–0.45, p = 0.006). Reducing these risks and taking protective measures might reduce the risk for influenza (H5N1) infection in backyard chickens.